LncRNAs signatures associated with cuproptosis predict the prognosis of endometrial cancer - Qi, Shiyuan; Feng, Huiyan; Li, Xiaomao (Frontiers in Genetics, 2023)
Background: Endometrial cancer (UCEC) is the sixth most common cancer in women, and although surgery can provide a good prognosis for early-stage patients, the 5-year overall survival rate for women with metastatic disease is as low as 16%. Long non-coding RNAs (LncRNAs) are thought to play an important role in tumor progression. Cuproptosis is a recently discovered form of cell death in which copper binds directly to the lipoacylated component of the tricarboxylic acid (TCA) cycle. The aggregation of these copper-bound listed mitochondrial proteins and the loss of Fe-S cluster proteins trigger proteotoxic stress, which leads to cell death. Therefore, the aim of this work was to investigate the role of Cuproptosis-related LncRNAs signaling in clinical prognostic prediction and immunotherapy, as well as the relationship between tumor mutational burden. Methods: Genomic, clinical and mutational data of endometrial cancer patients were presented in the TCGA database, and cuproptosis-related genes obtained from related studies. Coexpression analysis and Cox regression analysis were used to construct prognostic features. Patients were divided into high risk group and low risk group, and then ROC, survival rate, risk curve, principal component analysis, independent prognostic analysis and clinical subgroup model validation were performed to observe the prognostic value of characteristics. Subsequently, the GO and genomic KEGG enrichment and immune-related functions of LncRNAs as well as the tumor mutational burden were analyzed. Results: In 554 UCEC case data, we identified five associated LncRNAs co-expressed withcuproptosis genes, and we found that high-risk patients had poorer overall survival (OS), progression-free survival (PFS), and higher mortality. Independent prognostic analysis, ROC showed that the LncRNAs associated with cuproptosis could accurately predict the prognosis of patients.Enrichment analysis revealed that the biological functions of LncRNAs were related to tumorigenesis. We also discovered suppression of immune-related functions in high-risk patients with oncogene mutations, higher tumor mutational burden in low-risk patients, and longer overall survival in patients with higher tumor mutational burden. Conclusion: The identification of five LncRNAs associated with cuproptosis can accurately predict the prognosis of patients with endometrial cancer, and may provide a new perspective for clinical application and immunotherapy.